Ocean bottom pressure and circulation in the South Atlantic - Böning, Carmen; Timmermann, Ralph; Schröter, Jens; Macrander, Annecke (2007)
In order to obtain a better understanding of ocean mass variations and the circulationin the South Atlantic an analysis of ocean bottom pressure (OBP) fluctuationshas been performed. For this purpose we utilize a global ocean circulation model andcompare the simulated monthly mean OBP anomalies with in situ data measured bybottom pressure recorders (e.g. PIES) and data derived from gravity field anomaliesprovided by the GRACE satellite mission. The ocean model is a 1.5 global versionof the 3D Finite Element Sea Ice-Ocean Model (FESOM) which has been developedat the Alfred Wegener Institute for Polar and Marine Research (AWI). In situ dataof two PIES in the South Atlantic, which were deployed by the AWI in 2002 andrecovered in 2005, are available. First results indicate a strong correlation betweenFESOM and GRACE OBP anomalies on a global and regional scale. On smaller, synopticscales the correlation weakens. Due to spurious elongated meridional patternsin the monthly gravity field anomalies, gravity fluctuations on a scale less than 1000km are difficult to detect. Since the in situ measurements are point measurements bynature, it is essential to identify the area for which their time series are representative.A spatial cross-correlation analysis of FESOM data indicates that regions of spatiallycoherent patterns of OBP are separated by features of bottom topography. AveragingGRACE data over these patterns improves agreement with the in situ data. Time seriesof simulated volume transports between the two PIES positions are compared tototal ACC transport variations. Furthermore, the representation of the Southern AnnularMode in simulated bottom pressure variations along oceanographic sections, e.g.along the Greenwich Meridian and along a line between Cape Town and the ScotiaSea, is studied.